1998
DOI: 10.3133/ofr98494
|View full text |Cite
|
Sign up to set email alerts
|

Geologic map of the Alder Creek Quadrangle, Malheur County, Oregon

Abstract: rural and stratigraphic transition zone is located about 2 km west of the eastern boundary of the Alder Creek quadrangle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Clinoptilolite nearly completely replaces ash, and forms euhedral crystals in void space. Brooks and O'Brien (1992), Ferns and O'Brien (1992), Lees (1994), Binger (1997), Evans and Binger (1998a;, Johnson et al (1998), Evans and Binger (1999a;, Camp et al (2003), Nash and Perkins (2012), Ferns and McClaughry (2013), Coble and Mahood, in press, this study (see Appendix A for analyses and description of analytical technique).…”
Section: Fig 1 Regional Map Highlighting Mid-miocene (~17-15 Ma) Volcanic Rocks In the Pacificmentioning
confidence: 95%
“…Clinoptilolite nearly completely replaces ash, and forms euhedral crystals in void space. Brooks and O'Brien (1992), Ferns and O'Brien (1992), Lees (1994), Binger (1997), Evans and Binger (1998a;, Johnson et al (1998), Evans and Binger (1999a;, Camp et al (2003), Nash and Perkins (2012), Ferns and McClaughry (2013), Coble and Mahood, in press, this study (see Appendix A for analyses and description of analytical technique).…”
Section: Fig 1 Regional Map Highlighting Mid-miocene (~17-15 Ma) Volcanic Rocks In the Pacificmentioning
confidence: 95%
“…Close relationships in terms of time and space of lavas of Hunter Creek Basalt (i.e., upper Grand Ronde Basalt) with the Dinner Creek Tuff have been found ~20 km southeast of the proposed source area from where Evans (1990) and Evans and Binger (1998) reported a mafi c vitrophyric lense with Hunter Creek Basalt composition in Dinner Creek Tuff; they suggested that these two magmas may have erupted contemporaneously. We investigate this further and use our compositional glass data obtained on shards, pumice shards, mafi c globules , and pumices that we found in one of the two 15.5 Ma cooling units (unit 2) and in the 14.9 Ma ignimbrite (unit 4).…”
Section: Mafi C Dinner Creek Tuff: Records Of Grande Ronde Basalt Magmasmentioning
confidence: 96%
“…2) Kittleman et al (1965Kittleman et al ( , 1967, a 15.5 Ma rhyolite-dacite tuff (Sales et al, 2017). The icelandite of Alder Creek occupies the same stratigraphic position as the Hunter Creek Basalt (Kittleman et al, 1965(Kittleman et al, , 1967Evans and Binger, 1999c) and seemingly provides evidence of mixing of upper Littlefield Rhyolite and Hunter Creek Basalt magmas (see below and cf. Figs.…”
Section: Southern Stratigraphic Transect In Alder Creek Canyonmentioning
confidence: 98%